Pediatric urology for the primary care physician - Hulbert, William C.; Mevorach, Robert A.; Rabinowitz, Ronald (Current Clinical Urology,, 2014)
While there are Pediatric Urology texts for pediatric urologists and for general urologists, there are none for primary care physicians. This book is written specifically for the primary care physician, the initial contact for the many children with urologic conditions. The text will assist the primary care physician in the recognition of and participation in the care of children with these common problems including both congenital and acquired conditions. Specific chapters are also dedicated to the management of cases that may include medical and/or surgical intervention. The contributing authors of this text were selected for their internationally recognized expertise and straight forward educational styles in the field of Pediatric Urology. Pediatric Urology for the Primary Care Physician will significantly help our primary care colleagues in the evaluation and management of children with genito-urinary problems.